1991
DOI: 10.1159/000133146
|View full text |Cite
|
Sign up to set email alerts
|

Failure of chromosomally abnormal sperm to participate in fertilization in the Chinese hamster

Abstract: The selection of chromosomally abnormal gametes was investigated in the Chinese hamster by direct chromosome analysis of meiotic cells and one-cell embryos obtained from crossing heterozygotes for two reciprocal translocations, T(1;3)7Idr and T(1;3)8Idr. Expected frequencies of male and female gametes with different chromosome constitutions were estimated by scoring of secondary meiotic metaphase (MII) cells in the translocation heterozygotes. The frequency of gametes with each karyotype that participated in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…It is not yet clear if sperm selection plays an active role in in vivo fertilization. It has been repeatedly demonstrated that sperm with an abnormal chromosomal constitution are capable of fertilizing oocytes (Epstein and Travis, 1979;Sonta et al, 1984;Tates and de Boer, 1984), but other studies have shown the failure of sperm with a certain chromosomal constitution to participate in fertilization (Aranha and Martin-DeLeon, 1991;Sonta et al, 1991;Chayko and Martin-DeLeon, 1992). Although sperm karyotyping does involve in vitro fertilization of nonhuman oocytes, results obtained do not support the idea of selection based on the chromosomal content of sperm.…”
Section: Discussionmentioning
confidence: 96%
“…It is not yet clear if sperm selection plays an active role in in vivo fertilization. It has been repeatedly demonstrated that sperm with an abnormal chromosomal constitution are capable of fertilizing oocytes (Epstein and Travis, 1979;Sonta et al, 1984;Tates and de Boer, 1984), but other studies have shown the failure of sperm with a certain chromosomal constitution to participate in fertilization (Aranha and Martin-DeLeon, 1991;Sonta et al, 1991;Chayko and Martin-DeLeon, 1992). Although sperm karyotyping does involve in vitro fertilization of nonhuman oocytes, results obtained do not support the idea of selection based on the chromosomal content of sperm.…”
Section: Discussionmentioning
confidence: 96%
“…However, it remains possible that aneuploidy for other chromosomes and other types of chromosomal abnormalities may affect sperm maturation and fertilizing capacity. Indeed, results obtained with translocation carriers in Chinese hamsters suggested that sperm carrying specific chromosomal imbalances failed to participate in fertilization (Sonta et al, 1991; Sonta, 2004).…”
Section: Methods For Investigating Paternally‐transmitted Chromosomalmentioning
confidence: 99%
“…It would therefore be interesting to inves tigate the ability of cytogenetically unbalanced spermatozoa to take part in fertilization. Results obtained by Sonta et al (1991) with hamsters show that spermatozoa nullisomic for certain chromosome segments cannot fertilize ova. In contrast to these results, unbalanced embryos sired by heterozygous transloca tion carriers have been observed in pigs (King et al.…”
Section: I L I »mentioning
confidence: 98%